In vivo imaging of the time-dependent apparent diffusional kurtosis in the human calf muscle - Marschar, Anja Maria; Kuder, Tristan Anselm; Stieltjes, Bram; Nagel, Armin Michael; Bachert, Peter; Laun, Frederik Bernd (Journal of Magnetic Resonance Imaging, 2015)
Purpose: To evaluate the time dependency of apparent diffusion coefficient Dapp and apparent diffusional kurtosis Kapp in vivo in the human calf. Materials and Methods: Diffusion-weighted images of five healthy male volunteers were acquired using a 1.5T MR scanner. A stimulated echo sequence with echo planar imaging readout was used with diffusion gradients oriented along the three main axes. Mixing times (TM) of 100, 300, 500, and 700 ms and b-values ranging from 0 to 5600 s/mm2 were used. Dapp and Kapp were determined. Results: Dapp and Kapp decreased with increasing TM. As an example for absolute values, Dapp of the tibialis anterior drops from 1.18 ± 0.04 μm2/ms (TM = 100 ms) to 0.86 ± 0.02 μm2/ms (TM = 700 ms) (P = 0.001) and Kapp from 0.38 ± 0.06 to 0.32 ± 0.03 (P = 0.046) for a diffusion weighting along the left-right direction. Kapp was smaller than 0.43 in all muscles and at all TMs. Conclusion: The clearly observed time-dependence of Dapp and Kapp is an indicator of restricted diffusion in muscle tissue and may thus be a promising marker to investigate alterations of the microstructure. Compared to typical kurtosis values in white matter tissue of the brain, the kurtosis in muscle tissue is much smaller, which we attribute to the absence of the almost impermeable myelin sheath.
CRIS-Team Scopus Importer:2022-08-05
Keywords: calf muscle; diffusion; kurtosis; time-dependence